Tobacco Smoking a Potential Risk Factor in Transmission of COVID-19 Infection - Ahmed, Naseer (Pak J Med Sci, 2020)
Corona Virus disease 2019 (COVID-19) is a global pandemic and is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) group of viruses. To date, April 25, 2020, more than 2.4 million humans are infected and more than a hundred thousand deaths have been reported from more than 200 countries from COVID-19. There is no evidence-based treatment for the infection and prevention of transmission using social distancing, isolation and hygiene measures is widely recommended. Tobacco smoking is rampant in communities around the globe and the addiction to tobacco results in deaths of more than 8 million individuals each year. As COVID-19 transmits through salivary droplets and causes severe lung pneumonia, tobacco smokers are also at high risk of severe COVID-19 infection due to poor lung function, cross-infection and susceptible hygiene habits. Smoking tobacco (cigarette, e-cigarettes or waterpipe) produces exhaled smoke, coughing or sneezing, aerosols containing SARS-CoV-2 in the surroundings and contaminating surfaces. Therefore, smoking tobacco is a possible mode of transmission for the virus for both active and passive smokers. Smoking should be considered a risk factor for the disease transmission until further availability of evidence and measures to limit its direct and indirect effects should be implemented within the community.